Implementation of QbD strategies in the inoculum expansion of a mAb production process. Issue 3 (3rd December 2020) - Böhl, Ole Jacob; Schellenberg, Jana; Bahnemann, Janina; Hitzmann, Bernd; Scheper, Thomas; Solle, Dörte
Abstract: The quality by design approach was introduced to the biopharmaceutical industry over 15 years ago. This principle is widely implemented in the characterization of monoclonal antibody production processes. Anyway, the early process phase, namely the inoculum expansion, was not yet investigated and characterized for most processes. In order to increase the understanding of early process parameter interactions and their influence on the later production process, a risk assessment followed by a design of experiments approach was conducted. The DoE included the critical parameters methotrexate (MTX) concentration, initial passage viable cell density and passage duration. Multivariate data analysis led to mathematical regression models and the establishment of a designated design space for the studied parameters. It was found that the passage duration as well as the initial viable cell density for each passage during the inoculum expansion have severe effects on the growth rate and viability of the early process phase. Furthermore, the variations during the inoculum expansion directly influenced the production process responses. This carry‐over of factor effects highlights the crucial impact of early process failures and the importance of process analysis and control during the first part of mAb production processes.